DRR Cafeteria Pre-Ordering Food System (DRRC-POFS) / Nur Zafirah Baharim - Baharim, Nur Zafirah (2017)
Online food ordering system has been used in many restaurants, especially in fast food restaurant, in order to facilitate their customers to order food. This paper discuss about an online pre-ordering food system which is the DRR Cafeteria Pre-Ordering Food System (DRRC-POFS) that have been developed for DRR Cafeteria to facilitate the student of UiTM Kuala Terengganu to order meals and for the staff to control the meals production. The online pre-ordering system is easily understand as the process of ordering food earlier a day or more so that the staff of the cafeteria can budget how much meals should be produce based on the order that has been made by the students. The Rapid Application Development (RAD) Model is applied in developing the DRR Cafeteria Pre-Ordering Food System. The RAD Model phases contains of requirement planning, system design, construction and cutover. The DRR Cafeteria Pre-Ordering Food System has been demonstrated to the two expertise to get the suggestions and comments. Besides that, the DRR Cafeteria Pre-Ordering Food System has also be tested within 32 respondents by the distribution of the questionnaire regarding the functionality of the system. Based on the feedback from the respondents, the highest mean for construct user interface is 4.19, effective is 4.25, ease of use is 4.23, usability is 4.13, efficiency is 4.00 and learnability is 3.97. Other than that, based on the results of the current study, there are several suggestions were obtained for the university management especially the cafeteria management to get the idea to increase students satisfaction with food services.